Refleksivna uporaba znanja v kontekstu praktičnega učenja - Kodele, Tadeja (Socialno delo, 2015)
Practical learning is an important support for future social workers as they integrate theoretical knowledge with practical work. For students, the Master programme "Social work with families" means an additional year of their education. It contributed to reflection on how to implement practice for the students who have already finished undergraduate study of social work. How to assure such a context of practical learning, that will help students get knowledge about their work and that they will be able to find words to describe users what they are doing to ensure their participation in working process? Practical learning for students, which was designed in the project "Helping families in community: co-creation of desired changes for reducing social exclusion and strengthening health", enabled students to use concepts of social work in practice, with the intensive support of mentors, and to lead the conversation with family competently. They realized that the theory is useful in practice and that it is an important support for social work with families. Practical learning increased reflexive use of knowledge in practice.
Keywords: social work; socialno delo; student practice; študijska praksa; družina; family; krožni proces; circular process; learning; učenje